THE OSCE BORDER MANAGEMENT STAFF COLLEGE - Raczkowski, Henryk (Przegląd Strategiczny, 2015)
Effective border management is a priority for OSCE participating States and partners. Taking into consideration states’ border security needs, it was of a crucial importance to develop systems and structures that respond to them. These are developed not only within states, but also within international organizations. The OSCE Member States initiated the Border Security and Management Concept: cooperation among the national agencies involved into border security and management on all the levels. One of the elements of this concept is the Border Management Staff College in Dushanbe.